2009
DOI: 10.1016/j.breast.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a 10-gauge vacuum-assisted system for ultrasound-guided excision of clinically benign breast lesions

Abstract: The aim of this study was to evaluate a 10-gauge vacuum-assisted system for the excision of clinically benign breast lesions. The minimal excision of 245 lesions in 162 patients was performed with VACORA vacuum-assisted system under the guidance of ultrasound between July 2007 and April 2008. The lesions were category 3 lesions as determined by ultrasound imaging according to Breast Imaging Reporting and Data System (BI-RADS) (n=208) or had been confirmed as benign by a previous core-needle biopsy (n=37). As m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…Our preliminary study has demonstrated the successful application of a 10‐gauge VAB system on the resection of benign breast lesions (21). Recently, a new vaccum‐assisted biopsy system with 7‐gauge needle emerged, which could provide a continuous resection function.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary study has demonstrated the successful application of a 10‐gauge VAB system on the resection of benign breast lesions (21). Recently, a new vaccum‐assisted biopsy system with 7‐gauge needle emerged, which could provide a continuous resection function.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are studies reporting this as the only correlation (6,7,14), but there are also studies which did not find this relationship (9).…”
Section: Discussionmentioning
confidence: 99%
“…Lesions, if not excised, require follow-up and can cause anxiety in patients (6). US guided VAB of breast lesions does not require hospitalization, is less invasive and cosmetically more pleasing (7). Especially in lesions smaller than 2 cm in size, success rates of 95-100% are reported.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases of non-invasive ductal carcinoma, the tumors could not be identified clearly on US (Evans 1992) or were found to display predominantly para-tumoral features such as ductal dilatation or irregularities (Li et al 2010). All of these features can be evaluated before performing CNB, and alternate methods should be implemented such as MMT or Vacora® (Salem et al 2009; Wang et al 2009; Hauth et al 2008), as stated in the text. On the other hand, several factors might disturb the process of acquiring appropriate tissue specimens for CNB, even when a clear view of the subject is achieved.…”
Section: Discussionmentioning
confidence: 99%